HUBUNGAN ANTARA PENYESUAIAN PERKAWINAN DENGAN KEHARMONISAN KELUARGA PADA AWAL PERKAWINAN PASANGAN BERSTATUS MAHASISWA - Rachmawati, Susi (Universitas Sahid Surakarta, 2014)
Once the importance of family harmony for the development of the younger generation of the child as a member of the family, so expect every couple to seek the harmony and harmony in the family. The population in this study were all female students who have been married at UMS in 9 subjects the faculty of Health Sciences, Faculty of Psychology 13 subjects, FKIP 11 subjects, 3 subjects Faculty of Law, Faculty of Economics 4 subjects, all of which amounts to 40 subjects. The sampling technique population studies. Measuring tool used to reveal the research variables there are two kinds of measuring instruments, namely: (1) the scale of family harmony, and (2) marital adjustment scale. Analysis of the data in this study using product moment correlation.Based on the analysis of the obtained highly significant correlation between marital adjustment with family harmony or rxy of 0.439 with p <0.01, which means there is a very significant positive correlation between marital adjustment to family harmony. The better the adjustment of individual marriage, the higher the harmony of the family, and vice versa. Mean empirical marital adjustment variable with a mean of 123.750 hypothetical average of 105. So the empirical> hypothetical average which means generally the subject of a student partner marital adjustment in the categorization UMS high, while empirical variables family harmony at 137.425 with a hypothetical average of 110. So the empirical mean > hypothetical average which means generally the subject has a high family harmony. The role of marital adjustment to the harmony of the family (SE) of 19.3%. It was concluded that there was a significant positive correlation between marital adjustment to family harmony.Keywords: Redefining marriage, family harmony